"Fundamental" "Constants" and Precision Tests of the Standard Model. Issue 5 (25th December 2022) - Koberinski, Adam
Abstract: I provide an account of precision testing in particle physics that makes a virtue of theory-ladenness in experiments. Combining recent work on the philosophy of experimentation with a broader view of the scientific process allows one to understand that the most precise and secure knowledge produced in a mature science cannot be achieved in a theory-independent fashion. I discuss precision tests of the muon's magnetic moment and effective field theory as a means to repurpose precision tests for exploratory purposes.